Integrating Literacy and Engineering Instruction for Young Learners - Wilson-Lopez, Amy; Gregory, Stacie (The Reading teacher, 2015)
According to recently published national standards, elementary students should engage in engineering design activities. This article outlines ways that teachers can use literacy instruction to support young students’ engineering design activity, such as by selecting texts in which characters face problems that can be solved through engineering, providing students with opportunities to practice comprehension strategies while reading those texts, and modeling for them how to write a variety of texts that are relevant to engineers’ practices. The authors describe how they integrated this type of literacy instruction into engineering units in third‐ and fifth‐grade classrooms.